2019
DOI: 10.1016/j.gie.2019.04.215
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for early and late adenoma recurrence with regard to the histological margin

Abstract: no severe or serious adverse events or deaths were registered. Given the observational nature of our study, assessment of blood electrolyte or creatinine was not feasible. Nevertheless, no clinical event attributable to electrolyte imbalance or dehydration was observed in any patient, confirming good safety of NER1006 in a real-life setting. Regarding concerns about the use of NER1006 in the elderly, 45% of the patients in our cohort were >65 years old, and among those the median age was 73.6 AE 6.1 years (ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This study has a significant guiding value for primary prevention and early diagnosis of colorectal cancer by carrying out retrospective analysis and adopting multivariate logistic analysis on risk factors affecting the adenoma risk grade in patients with intestinal polyps, aiming to fully understand the rules of occurrence and development of intestinal polyps and to implement early intervention [ 19 , 20 ]. In this study, gender was found to be an independent risk factor for high-grade adenoma in patients with intestinal polyps, but this indicator is somewhat controversial among studies; some reported [ 21 ] that the incidence of high-grade adenoma in male patients with intestinal polyps was significantly higher than that in female patients, which might be due to their bad living habits such as drinking and smoking [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study has a significant guiding value for primary prevention and early diagnosis of colorectal cancer by carrying out retrospective analysis and adopting multivariate logistic analysis on risk factors affecting the adenoma risk grade in patients with intestinal polyps, aiming to fully understand the rules of occurrence and development of intestinal polyps and to implement early intervention [ 19 , 20 ]. In this study, gender was found to be an independent risk factor for high-grade adenoma in patients with intestinal polyps, but this indicator is somewhat controversial among studies; some reported [ 21 ] that the incidence of high-grade adenoma in male patients with intestinal polyps was significantly higher than that in female patients, which might be due to their bad living habits such as drinking and smoking [ 22 ].…”
Section: Discussionmentioning
confidence: 99%